Literatur Review: Analisis Pengembangan Media Pembelajaran dalam Mata Pelajaran IPA Materi Pesawat Sederhana pada Siswa Sekolah Dasar - Suci Handhayani; Zahri Kurniawan; Indah Putri Yani; Wahyu Kurniawati (STIKes Ibnu Sina Ajibarang, 2024)
One of the primary school subjects that is compulsory for students to study is Natural Sciences (IPA). In conducting the learning process a teacher needs to prepare models and methods as well as what media is chosen to help the teacher deliver the material. So that students can receive the material well and work the matter properly and improve the student's learning outcomes from before learning to after learning. This research is to find out what models and media can be applied in IPA learning on simple aircraft material. This article is written using the research method of a library review. This research includes the study of libraries to gather information and analyze literature. Of the eight articles scanned with one or two using similar learning models and other learning media showed positive results for students and teachers. Improved student learning about simple aircraft material became better. Some models and learning media on simple aircraft material are a reference to teachers in implementing the IPA learning process well and achieving the entire learning plan.